PEMBUATAN ECOBRICK SEBAGAI BARANG TEPAT GUNA DAN UPAYA MENGURANGI SAMPAH - Asral, Asral; Rahmat Ramadhan; Wira Azri Perdana; Muhammad Naufal Anshori Surzai; Abiyu Fathoni; Devita Sari; Safika Sari; Sri Wahyuni Lino; Sarah Jaya Cita; Vira Aulia Rahmi (JURNAL PENGABDIAN MANDIRI, 2024)
Plastic waste is a pressing global issue. One viable solution is to repurpose plastic waste into crafts using the ecobrick method. Ecobricks are a creative technique to minimize plastic waste by transforming it into useful objects, while simultaneously reducing pollution and toxins. The plastic waste management program utilizing ecobricks in Desa Mumpa, Kec. Tempuling, aims to increase children's awareness of the importance of creativity in maintaining a clean and healthy environment. The outcome of this program is heightened community awareness, especially among children, about managing waste through recycling into valuable products, while realizing that waste management is a shared responsibility. This activity also fosters their creativity in utilizing available waste.